Reciprocal interactions among Cobll1, PACSIN2, and SH3BP1 regulate drug resistance in chronic myeloid leukemia - Park, Kibeom; Yoo, Hee Seop; Oh, Chang Kyu; Lee, Joo Rak; Chung, Hee Jin; Kim, Ha Neul; Kim, Soo Hyun; Kee, Kyung Mi; Kim, Tong Yoon; Kim, Myungshin; Kim, Byung Gyu; Ra, Jae Sun; et al. (Cancer Medicine, 2022)
Cobll1 affects blast crisis (BC) progression and tyrosine kinase inhibitor (TKI) resistance in chronic myeloid leukemia (CML). PACSIN2, a novel Cobll1 binding protein, activates TKI-induced apoptosis in K562 cells, and this activation is suppressed by Cobll1 through the interaction between PACSIN2 and Cobll1. PACSIN2 also binds and inhibits SH3BP1 which activates the downstream Rac1 pathway and induces TKI resistance. PACSIN2 competitively interacts with Cobll1 or SH3BP1 with a higher affinity for Cobll1. Cobll1 preferentially binds to PACSIN2, releasing SH3BP1 to promote the SH3BP1/Rac1 pathway and suppress TKI-mediated apoptosis and eventually leading to TKI resistance. Similar interactions among Cobll1, PACSIN2, and SH3BP1 control hematopoiesis during vertebrate embryogenesis. Clinical analysis showed that most patients with CML have Cobll1 and SH3BP1 expression at the BC phase and BC patients with Cobll1 and SH3BP1 expression showed severe progression with a higher blast percentage than those without any Cobll1, PACSIN2, or SH3BP1 expression. Our study details the molecular mechanism of the Cobll1/PACSIN2/SH3BP1 pathway in regulating drug resistance and BC progression in CML.
Keywords: Adaptor Proteins, Signal Transducing; Apoptosis; Blast Crisis; Drug Resistance; Drug Resistance, Neoplasm; GTPase-Activating Proteins; Humans; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Protein Kinase Inhibitors; blastic transformation; chronic myeloid leukemia; Cobll1; PACSIN2; SH3BP1